Β-Carotene-9′, 10′-Oxygenase Status Modulates the Impact of Dietary Tomato and Lycopene on Hepatic Nuclear Receptor–, Stress-, and Metabolism-Related Gene Expression in Mice. Issue 4 (19th February 2014) - Tan, Hsueh-Li; Moran, Nancy E.; Cichon, Morgan J.; Riedl, Ken M.; Schwartz, Steven J.; Erdman, John W.; Pearl, Dennis K.; Thomas-Ahner, Jennifer M.; Clinton, Steven K.
Abstract: Tomato and lycopene (ψ, ψ-carotene) consumption is hypothesized to protect against nonalcoholic steatohepatitis and hepatocarcinogenesis, processes that may depend upon diet and gene interactions. To investigate the interaction of tomato or lycopene feeding with β-carotene-9′, 10′-monooxygenase ( Bco2 ) on hepatic metabolic and signaling pathways, male wild-type (WT) and Bco2 −/− mice (3-wk-old; n = 36) were fed semi-purified control, 10% tomato powder–containing, or 0.25% lycopene beadlet–containing diets for 3 wk. Serum lycopene concentrations were higher in lycopene- and tomato-fed Bco2 −/− mice compared with WT ( P = 0.03). Tomato- and lycopene-fed mice had detectable hepatic apolipoprotein (apo)-6′-, apo-8′-, and apo-12′-lycopenal concentrations. Hepatic expression of β-carotene-15, 15'-monooxygenase was increased in Bco2 −/− mice compared with WT ( P = 0.02), but not affected by diet. Evaluation of hepatic gene expression by focused quantitative reverse transcriptase-polymerase chain reaction arrays for nuclear receptors and coregulators (84 genes) and stress and metabolism (82 genes) genes indicates that tomato feeding affected 31 genes (≥1.5-fold, P < 0.05) and lycopene feeding affected 19 genes, 16 of which were affected by both diets. Lycopene down-regulation of 7 nuclear receptors and coregulators, estrogen-related receptor-α, histone deacetylase 3, nuclear receptor coactivator 4, RevErbA-β, glucocorticoid receptor, peroxisome proliferator-activated receptor (PPAR)-α, and PPAR-γ, coactivator 1 β was dependent upon interaction with Bco2 status. Lycopene and tomato feeding induced gene expression patterns consistent with decreased lipid uptake, decreased cell proliferation and mitosis, down-regulated aryl hydrocarbon receptor signaling, and decreased expression of genes involved in retinoid X receptor heterodimer activation. Tomato feeding also caused expression changes consistent with down-regulation of DNA synthesis and terpenoid metabolism. These data suggest tomato components, particularly lycopene, affect hepatic gene expression, potentially affecting hepatic responses to metabolic, infectious, or chemical stress.